2015
DOI: 10.1016/j.pmedr.2015.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood disadvantage, physical activity barriers, and physical activity among African American breast cancer survivors

Abstract: Background In view of evidence that African American cancer survivors experience the greatest challenges in maintaining adequate levels of physical activity, this cross-section study was designed to determine whether individual and residential environment characteristics are associated with physical activity in this population. Methods A total of 275 breast cancer survivors completed self-report items measuring sociodemographic variables, physical activity, and select barriers to physical activity in Spring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…Younger women reported higher mean scores for having a lack of time and energy than did older women; less educated women reported higher mean scores for feeling discouraged and having fear of injury, equipment, facilities and good health; while obese women had a higher mean score for feeling discouraged and having a lack of facilities. Another study that utilized the same group of participants to examine the association between neighborhood characteristics and PA (Jones and Paxton 2015), revealed that median household income and the percentage of households who rent were associated with PA. Increase in median household income resulted in increase in PA MET-minutes/week; and when the percentage of households who rent increases, the PA MET-minutes/week decreased. Diggins et al (2016) reported that 40.2% AA BCSs engaged in PA.…”
Section: Discussionmentioning
confidence: 99%
“…Younger women reported higher mean scores for having a lack of time and energy than did older women; less educated women reported higher mean scores for feeling discouraged and having fear of injury, equipment, facilities and good health; while obese women had a higher mean score for feeling discouraged and having a lack of facilities. Another study that utilized the same group of participants to examine the association between neighborhood characteristics and PA (Jones and Paxton 2015), revealed that median household income and the percentage of households who rent were associated with PA. Increase in median household income resulted in increase in PA MET-minutes/week; and when the percentage of households who rent increases, the PA MET-minutes/week decreased. Diggins et al (2016) reported that 40.2% AA BCSs engaged in PA.…”
Section: Discussionmentioning
confidence: 99%
“…Although survivors seem to perceive barriers to health behaviours across multiple levels, only a handful of studies have sought to examine whether the existence of barriers at a specific level influences survivors’ actual health behaviours (Ottenbacher et al, 2011; Jones & Paxton, 2015; Oyekanmi & Paxton, 2014; the latter two studies used the same sample). For example, breast cancer survivors perceiving barriers at the social- or environmental-level (e.g., ‘no one to exercise with’, ‘nowhere to do it’), as well as those at the individual-level (e.g., ‘not sure what to do’, ‘don’t want to get sore’, ‘no willpower’) reported fewer minutes of self-reported physical activity (occupational and leisure physical activity/week) than did those who did not report these barriers (Ottenbacher et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For example, breast cancer survivors perceiving barriers at the social- or environmental-level (e.g., ‘no one to exercise with’, ‘nowhere to do it’), as well as those at the individual-level (e.g., ‘not sure what to do’, ‘don’t want to get sore’, ‘no willpower’) reported fewer minutes of self-reported physical activity (occupational and leisure physical activity/week) than did those who did not report these barriers (Ottenbacher et al, 2011). Also, besides ‘lack of interest’, ‘lack of facilities/space’ was associated with fewer minutes of self-reported physical activity (combined mild, moderate, and vigorous/week) among African American breast cancer survivors (Jones & Paxton, 2015). These results imply that not only individual- but also higher-level barriers should be considered when designing an intervention that aims to promote breast cancer survivors’ physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…22, 23 Understanding the perceptions of prolonged sitting in African American breast cancer survivors may help to understand the unique opportunities and potential challenges that will need to be considered prior to developing interventions to reduce prolonged sitting.…”
Section: Introductionmentioning
confidence: 99%